Ferrite powder and method for producing the same
By adding α-Fe2O3 to the ferrite powder, the problem of low voltage resistance in the resin composition of spherical particle ferrite powder is solved, and the effect of high voltage resistance and excellent magnetic characteristics at high filling rate is achieved.
Patent Information
- Application Number
- CN202180010387.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-27
- Filing Date
- 2021-01-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-01-27
AI Technical Summary
When the ferrite powder made of spherical particles produced by spraying method is mixed with the resin to make a resin composition, the ferrite powder has a problem of low voltage resistance, and is more obvious, especially when the filling rate is high.
By containing a predetermined amount of α-Fe2O3 in the ferrite powder, the resistance can be increased while maintaining magnetic characteristics, thereby maintaining a high withstand voltage in the resin composition with a high filling rate.
Maintaining high voltage withstand voltage and excellent magnetic properties in high fill rate resin compositions is achieved, and the problem of low voltage withstand voltage in the prior art is solved.
Smart Images

Figure BDA0003757684980000071 
Figure BDA0003757684980000121 
Figure BDA0003757684980000201
Abstract
Description
Technical Field
[0001] The present invention relates to ferrite powder and a method for producing the same. Background Art
[0002] Ferrite resin composite materials (resin compositions) composed of ferrite powder and resin are widely used in various applications represented by electromagnetic wave shielding materials. The composite material is made by mixing ferrite powder as a filler with a resin, and is formed into a shape of a sheet or the like to become a molded body (composite). At this time, if the shape of the particles constituting the ferrite powder is close to a sphere, the fluidity during molding increases, and the filling rate of the ferrite powder in the composite increases. Therefore, the formability becomes good, and the characteristics such as electromagnetic wave shielding performance are excellent. From this point of view, focusing on ferrite powder composed of spherical particles, a scheme for making such spherical particles by a spraying method is proposed.
[0003] For example, Patent Document 1 (International Publication No. 2017 / 212997) discloses a ferrite particle, which is a single crystal ferrite particle with an average particle size of 1 to 2000 nm and a perfect spherical particle shape, characterized in that the ferrite particle contains substantially no Zn, contains 3 to 25 weight % Mn, and contains 43 to 65 weight % Fe, and the real part μ' of the complex magnetic permeability measured by a molded body composed of the ferrite particles and a binder resin has a maximum value in the frequency band of 100 MHz to 1 GHz (Claim 1 of Patent Document 1). In addition, Patent Document 1 describes the following: a granulated material composed of a ferrite raw material is ferritized by spraying it in the atmosphere, and then, after rapid cooling and solidification, only particles having a particle size within a specified range are recovered to produce a material that, when used as an electromagnetic wave shielding material for electronic equipment, can stably shield electromagnetic waves of a wide frequency band that needs to be shielded regardless of the frequency (Patent Document 1
[0039] and
[0078] ).
[0004] Patent document 2 (International Publication No. 2017 / 169316) discloses a ferrite particle characterized by being a single crystal Mn-based ferrite particle with an average particle size of 1 to 2000 nm and a true spherical particle shape, and a saturation magnetization of 45 to 95 Am 2 / kg (claim 1 of Patent Document 2). In addition, Patent Document 2 also describes the following: a ferrite raw material containing Mn and Fe is sprayed in the atmosphere to form a ferrite, and then, after rapid solidification, only particles with a particle size within a predetermined range are recovered to obtain a higher saturation magnetization and excellent dispersibility in a resin, a solvent or a resin composition (Patent Document 2,
[0033] and
[0089] ).
[0005] Patent document 3 (Japanese Patent Publication No. 2016-060682) discloses a spherical ferrite powder, characterized in that it contains ferrite particles with a particle size of less than 11 μm at a rate of 15 to 30% by weight, and the volume average particle size is 10 to 50 μm. The following contents are recorded: the adjusted granules are sprayed in the atmosphere to make them ferrite, and when used as a filler, the filling and moldability are good, the workability is excellent, and the resistance is high. Therefore, the spherical ferrite powder is made into a resin composition together with a resin, and the molded body formed can be used in various applications represented by IC sealants for electromagnetic wave absorption (claims 1,
[0058] and
[0093] of patent document 3).
[0006] Patent document 4 (Japanese Patent Gazette No. 2005-015303) discloses a method for producing spherical powder, which is characterized in that it includes: a surface treatment step, in which the raw material powder is surface treated by heating a treatment agent composed of a raw material powder and at least one of a higher fatty acid, a derivative thereof, a higher hydrocarbon, and a higher alcohol to a specified temperature and then stirring the treatment agent; and a spherical powder generation step, in which the raw material powder after the surface treatment is put into a combustion flame generated in a combustion furnace and melted to form a spheroid, and the raw material powder is further moved to the outside of the combustion flame and solidified to obtain a spherical powder (claim 1 of patent document 4).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2017 / 212997
[0010] Patent Document 2: International Publication No. 2017 / 169316
[0011] Patent Document 3: Japanese Patent Application Publication No. 2016-060682
[0012] Patent Document 4: Japanese Patent Application Publication No. 2005-015303 Summary of the invention
[0013] Technical problem to be solved by the invention
[0014] However, the inventors of the present invention have found that the ferrite powder composed of spherical particles made by the spraying method has a low resistance, and when it is mixed with a resin to make a resin composition, there are sometimes problems in terms of withstand voltage (breakdown voltage). Especially when the filling rate of the ferrite powder is high, the withstand voltage of the resin composition is reduced. If the withstand voltage of the resin composition is low, the resin composition causes insulation breakdown when a voltage is applied, which is problematic as a component.
[0015] The inventors of the present invention have further studied and obtained the following insights: by making a ferrite powder composed of spherical particles contain a specified amount of α-Fe2O3, the electrical resistance can be increased while maintaining the magnetic properties (saturation magnetization, magnetic permeability) of the ferrite powder at a high level, and when the ferrite powder is applied to a resin composition, a high withstand voltage can be maintained even at a high filling rate.
[0016] The present invention has been accomplished based on such findings, and an object of the present invention is to provide a ferrite powder and a method for producing the same, which have high magnetic properties and electrical resistance and can maintain a high withstand voltage even when used in a resin composition having a high filling rate.
[0017] Technical means for solving technical problems
[0018] The present invention includes the following aspects (1) to (7). It should be noted that in this specification, the expression "to" includes both numerical values. That is, "X to Y" is synonymous with "X or more and Y or less".
[0019] (1) A ferrite powder comprising true spherical ferrite particles,
[0020] The ferrite powder contains iron (Fe): 55.0-70.0 mass % and manganese (Mn): 3.5-18.5 mass %, and the amount of α-Fe2O3 is higher than 0.0 mass % and less than 7.5 mass %,
[0021] The volume average particle size D50 of the ferrite powder is 15.0 μm or less.
[0022] (2) In the ferrite powder according to (1) above, the amount of α-Fe 2 O 3 is 3.0 mass % or more and 6.0 mass % or less.
[0023] (3) In the ferrite powder according to (1) or (2) above, the volume average particle size D50 is 2.0 μm or more.
[0024] (4) The ferrite powder according to any one of (1) to (3) above, wherein the average shape factor SF-1 of the ferrite powder is 100 to 110.
[0025] (5) The ferrite powder according to any one of (1) to (4) above, wherein the carbon (C) content of the ferrite powder is 0.12 mass % or less.
[0026] (6) The ferrite powder according to any one of (1) to (5) above, wherein the volume resistivity of the ferrite powder is 1.0×10 8 Ω·cm or more.
[0027] (7) A method for producing the ferrite powder according to any one of (1) to (6) above, comprising the following steps:
[0028] A process of mixing ferrite raw materials to prepare a raw material mixture;
[0029] The process of pre-calcining the raw material mixture to obtain a pre-calcined product;
[0030] A step of crushing and granulating the calcined product to obtain a granulated product; and
[0031] a step of spraying the granulated material to obtain a sprayed material,
[0032] The carbon content of the granulated material is set to 0.001 to 0.095% by mass. In the thermal spraying step, the raw material supply rate is set to 2.5 to 9.0 kg / hour, and the combustion gas flow rate is set to 3 to 10 m / s. 3 / hour, set the oxygen flow rate to 18~60m 3 / Hour.
[0033] Effects of the Invention
[0034] According to the present invention, there are provided a ferrite powder having high magnetic properties and electrical resistance and capable of maintaining a high withstand voltage even when used in a resin composition having a high filling rate, and a method for producing the same. DETAILED DESCRIPTION
[0035] A specific embodiment of the present invention (hereinafter referred to as "this embodiment") will be described. The present invention is not limited to the following embodiment, and various modifications can be made within the scope of the present invention.
[0036] Ferrite powder
[0037] The ferrite powder of the present embodiment is composed of true spherical ferrite particles. That is, the ferrite powder includes a plurality of true spherical ferrite particles. By being composed of true spherical ferrite particles, the ferrite powder can have excellent formability and filling properties when used as a filler in a resin composition (ferrite resin composite material). The spherical particles smoothly avoid contact with other particles during molding. Therefore, the fluidity during molding is good and the particles are densely filled. In contrast, particles with anisotropic shapes (indeterminate shapes) such as plate-like or needle-like shapes have poor formability and filling properties. In addition, in this specification, indeterminate shaped particles include anisotropic shaped particles, which are used in contrast to fixed shaped particles such as spherical particles.
[0038] The ferrite powder of the present embodiment contains 55.0-70.0 mass % of iron (Fe) and 3.5-18.5 mass % of manganese (Mn). The ferrite powder has a component of manganese (Mn) ferrite. When the iron (Fe) content of manganese (Mn) ferrite is too little or the manganese (Mn) content is too much, the saturation magnetization (σs) of manganese (Mn) ferrite will decrease, or the imaginary part of the magnetic permeability (μ") and the loss coefficient (tanδ) will increase. Therefore, when the ferrite powder is applied to the resin composition, the saturation magnetic flux density may decrease or the loss may increase. On the other hand, when the iron (Fe) content is too much or the manganese (Mn) content is too little, the ferrite composition is close to magnetite. Magnetite (FeO·Fe2O3) contains unstable divalent iron ions (Fe 2+ ), so the saturation magnetization (σs) may be reduced due to oxidation. From this point of view, the iron (Fe) and manganese (Mn) contents of the ferrite powder are limited to the above ranges. The ferrite powder may contain 57.0 to 70.0% by weight of iron (Fe) and 4.5 to 15.0% by weight of manganese (Mn), or 58.0 to 69.0% by weight of iron (Fe) and 6.0 to 10.0% by weight of manganese (Mn). The total value of iron (Fe) and manganese (Mn) will not exceed 73.0% by weight.
[0039] Ferrite is an oxide. Therefore, ferrite powder contains oxygen (O) in addition to iron (Fe) and manganese (Mn). In addition, in the case of satisfying the above-mentioned component range, other components other than iron (Fe), manganese (Mn) and oxygen (O) may also be included. As such components, for example, zinc (Zn), magnesium (Mg), strontium (Sr), titanium (Ti), lithium (Li), barium (Ba), yttrium (Y), nickel (Ni), copper (Cu), cobalt (Co), etc. can be cited. However, from the perspective of fully exerting the characteristics of manganese (Mn) ferrite, the content of other components is preferably less than 1.0 mass%, and more preferably less than 0.5 mass%. Ferrite powder contains iron (Fe), manganese (Mn) and oxygen (O), and the remainder may have a component of inevitable impurities. Here, inevitable impurities are components that are inevitably mixed in the manufacturing process, and refer to components whose content is less than 5000ppm. Examples of unavoidable impurities include silicon (Si), aluminum (Al), calcium (Ca), chlorine (Cl), boron (B), zirconium (Zr), and chromium (Cr).
[0040] The amount of α-Fe2O3 in the ferrite powder of the present embodiment is higher than 0.0 mass % and less than 7.5 mass %. By making it contain α-Fe2O3 (hematite), it is possible to suppress the reduction of resistance and withstand voltage while maintaining the higher magnetic properties of the ferrite powder. The reason is as follows. When the ferrite is manufactured, the iron (Fe) component used as the raw material reacts with transition metal components such as manganese (Mn) to form a ferrite component such as the spinel phase which is a strong magnet. The spinel phase is a composite oxide containing divalent metal ions and trivalent metal ions such as manganese ferrite ((Mn, Fe)O·(Mn, Fe)2O3) or magnetite (FeO·Fe2O3). Here, manganese (Mn) ions and iron (Fe) ions can take any valence of divalent and trivalent. Therefore, the electron jumping phenomenon is caused in the spinel phase, and conductivity occurs. As a result, the resistance of ferrite composed only of the spinel phase, especially manganese (Mn) ferrite, tends to decrease.
[0041] In contrast, α-Fe2O3 (hematite) is free iron oxide derived from the iron (Fe) component that has not formed a spinel phase. α-Fe2O3 contains trivalent iron ions (Fe 3+ ), but does not contain divalent iron ions (Fe 2+ ). Therefore, it is a stable compound with high resistance. Therefore, by including α-Fe2O3 in the positive spherical ferrite particles in the ferrite powder, the conductive path based on the spinel phase is cut off, and the resistance and withstand voltage are increased. Therefore, α-Fe2O3 is limited to an essential component, that is, the amount of α-Fe2O3 is limited to more than 0.0 mass%. The amount of α-Fe2O3 can be more than 0.1 mass%, or more than 0.5 mass%, or more than 1.0 mass%, or more than 2.0 mass%, or more than 3.0 mass%, or more than 4.0 mass%. On the other hand, unlike the spinel phase, α-Fe2O3 is a paramagnetic substance. Therefore, if the amount of α-Fe2O3 is too much, the magnetic properties (saturation magnetization, magnetic permeability) of the ferrite powder may decrease. The amount of α-Fe2O3 can be less than 7.0 mass%, or less than 6.0 mass%.
[0042] The ferrite powder (orthospherical ferrite particles) mainly includes a spinel phase in addition to α-Fe2O3. The content of the spinel phase can be 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more. In addition, the ferrite powder may also contain other phases or inevitable impurities other than the spinel phase and α-Fe2O3. As such phases, for example, residual manganese oxides (MnO, Mn2O3, Mn3O4, etc.) or iron oxides other than spinel (γ-Fe2O3, FeO, Mn3FeO8, etc.) can be cited. However, the ferrite powder may not contain other phases. That is, the ferrite powder may contain a spinel phase and α-Fe2O3, and the remainder is inevitable impurities. It should be noted that the inevitable impurities are components with a content of less than 5000 ppm as mentioned above. Furthermore, in the ferrite powder of this embodiment, the true spherical ferrite particles constituting the ferrite powder include α-Fe2O3. For example, α-Fe2O3 may also be dispersed inside the true spherical ferrite particles. Therefore, the ferrite powder is distinguished from a mixture of ferrite particles not containing α-Fe2O3 and α-Fe2O3.
[0043] The volume average particle size (D50) of the ferrite powder of the present embodiment is 15.0 μm or less. When D50 is higher than 15.0 μm, there is a problem that the loss factor (tan δ) becomes too large and the withstand voltage decreases. D50 may be 10.0 μm or less, or 7.0 μm or less. The lower limit of D50 is not particularly limited. However, by increasing D50 to a certain extent, the viscosity increase of the resin composition can be suppressed and the filler filling rate can be improved. D50 may be 2.0 μm or more, or 2.5 μm or more. The particle size distribution may have two or more peaks. Here, the so-called having two or more peaks means that when the volume particle size distribution is regarded as a function of the particle size, the differential (differential coefficient) of the function or the second or higher differential has a value of 0 (maximum point, inflection point, saddle point, etc.) There are two or more points (wherein the particle size is expressed in logarithmic form).
[0044] The ferrite powder preferably has an average shape factor SF-1 of 100 to 110. SF-1 is an index of the sphericity of the particles (powder), which is 100 for a perfect sphere and increases as it moves away from a sphere. By setting SF-1 to 110 or less, the fluidity of the powder increases, and the formability and filling properties are further improved. SF-1 may be 108 or less, 105 or less, or 103 or less.
[0045] The average shape factor SF-1 of the ferrite powder is obtained by calculating the shape factor SF-1 of each particle for a plurality of ferrite particles and calculating the average value. The SF-1 of a ferrite particle can be measured by measuring the horizontal Feret diameter R (unit: μm), the projected circumference L (unit: μm) and the projected area S (unit: μm) of the particle. 2 ), and is obtained according to the following formula (1).
[0046] [Mathematical formula 1]
[0047]
[0048] The ferrite powder preferably has a BET specific surface area of 0.01 to 3.00 m 2 / g. By setting the BET specific surface area to 3.00 m 2 / g or less, the aggregation of ferrite powder can be suppressed, and the moldability and filling properties can be further improved. On the other hand, by setting the BET specific surface area to 0.01m 2 / g or more, the generation of inter-particle voids can be suppressed, and the filling property is more excellent. In addition, by setting the BET specific surface area within the above range, the adhesion between the ferrite powder and the resin is better when it is applied to a composite material or a composite. The BET specific surface area can also be 0.10 to 2.00 m 2 / g.
[0049] The tap density of the ferrite powder is preferably 0.50 to 5.00 g / cm 3 By mixing small-diameter particles with large-diameter particles, the tap density can be increased, and as a result, the filling property of the ferrite powder is excellent as a whole. The tap density can also be 1.50 to 3.50 g / cm 3 .
[0050] The ferrite powder preferably has a carbon (C) content of 0.12% by mass or less. The carbon is mainly a component caused by residual carbon (C) compounds derived from organic components (dispersants, binder resins, etc.) added when the ferrite powder is manufactured. If the organic component added when the ferrite powder is manufactured is too little, the raw material supply during spraying is unstable, and irregular particles are easily mixed into the ferrite powder. Irregular particles become the cause of the deterioration of magnetic properties and filling properties. Therefore, the ferrite powder preferably contains a certain amount of carbon. The amount of carbon (C) can be more than 0.001% by mass, or more than 0.002% by mass, or more than 0.003% by mass. On the other hand, if too much carbon (C) is contained, when the ferrite powder is used as a filler in a resin composition, it may hinder the curing of the resin. Although the detailed mechanism is unclear, it is believed that because the residual carbon (C) compound derived from the organic component is a compound with a main chain without a functional group, it may react with the resin and have an adverse effect on curing. The carbon content may be 0.100 mass % or less, 0.080 mass % or less, 0.050 mass % or less, or 0.010 mass % or less.
[0051] Ferrite powder is preferably used as residual carbon (C) compound, including erucic acid amide (C 22 H 43 NO), butyl palmitate (C 20 H 40 O2) and butyl stearate (C 22 H 44 O2) is one or more compounds selected from the group consisting of. These compounds are mainly derived from the components of organic components (dispersants, binder resins, etc.) added when the ferrite powder is manufactured. If no organic components are added when the ferrite powder is manufactured, the magnetic properties of the ferrite powder may be reduced, and the filling property of the resin composition may also deteriorate.
[0052] The ferrite powder of this embodiment contains α-Fe2O3, so the resistance is relatively high. The volume resistance of the ferrite powder can be 1.0×10 8 Ω·cm or more, and may be 2.0×10 8 Ω·cm or more, and can also be 4.0×10 8 The upper limit of the volume resistivity is not particularly limited, but 1.0×10 10 Ω·cm or less is typical.
[0053] Ferrite powder can be used as a resin composition for electromagnetic wave shielding materials and the like by mixing it with resin as a filler. Here, the resistance of the resin, the ferrite powder containing α-Fe2O3, and the ferrite powder not containing α-Fe2O3 decreases in sequence. That is, the resistance of the resin is the highest, and the resistance of the ferrite powder not containing α-Fe2O3 is the lowest. In addition, in the resin composition, if the filling rate of the ferrite powder increases, the distance between the ferrite powders becomes shorter, and some of the ferrite powders are in contact with each other. Therefore, when the ferrite powder not containing α-Fe2O3 with a low resistance is used as a filler for a high-filling resin composition, the withstand voltage decreases. This is because when a voltage is applied, a conductive path is formed between the ferrite particles with a low resistance, which causes breakdown (insulation breakdown). In contrast, if the ferrite powder containing α-Fe2O3 with a high resistance is used as a filler, such a decrease in withstand voltage can be prevented.
[0054] In addition, the ferrite powder of the present embodiment is not limited to the amount of α-Fe2O3 as a paramagnetic material and the volume average particle size (D50), so it is possible to maintain higher magnetic properties (saturation magnetization, magnetic permeability), and the loss factor (tanδ) can be suppressed at a lower level. Therefore, the magnetic properties of the resin composition can be excellent. The saturation magnetization (σs) of the ferrite powder can be 65emu / g or more, or 70emu / g or more, or 75emu / g or more, or 80emu / g or more, or 85emu / g or more. The upper limit of the saturation magnetization (σs) is not particularly limited, but is typically 95emu / g or less. In addition, the tanδ of the ferrite powder at 100MHz can be 0.20 or less, or 0.13 or less, or 0.06 or less. The lower limit of tanδ is not particularly limited, but is typically 0.001 or more.
[0055] Method for producing ferrite powder
[0056] The method for manufacturing ferrite powder of the present embodiment has the following steps: a step of mixing ferrite raw materials to prepare a raw material mixture (raw material mixing step); a step of pre-calcining the obtained raw material mixture to prepare a pre-calcined product (pre-calcining step); a step of crushing and granulating the obtained pre-calcined product to prepare a granulated product (granulation step); and a step of spraying the obtained granulated product to prepare a sprayed product (spraying step). In addition, the carbon content of the granulated product is set to 0.001 to 0.095% by mass. In the spraying step, the spraying raw material supply rate is set to 2.5 to 9.0 kg / hour, and the combustion gas flow rate is set to 3 to 10 m 3 / hour, set the oxygen flow rate to 18~60m 3 / hour. The following is a detailed description of each process.
[0057] <Raw material mixing process>
[0058] Mix ferrite raw materials to prepare a raw material mixture. As the ferrite raw materials, known ferrite raw materials such as oxides, carbonates, hydroxides and / or chlorides can be used. For example, as iron (Fe) raw materials and manganese (Mn) raw materials, iron oxide (Fe2O3), manganese tetraoxide (Mn3O4) and / or manganese dioxide (MnO2) can be used. The mixing ratio of the raw materials is carried out in a manner to obtain a ferrite powder of the desired composition. The mixing of the raw materials can be carried out using a known mixer such as a Henschel mixer, and can be carried out by either or both of a dry method and a wet method. In addition, the raw material mixture can also be granulated (pre-granulated) using a granulating device such as a roller compactor.
[0059] <Pre-firing process>
[0060] In the pre-sintering step, the obtained raw material mixture is pre-sintered to prepare a pre-sintered product. The pre-sintering can be performed using a known method. For example, it can be performed using a furnace such as a rotary drying furnace, a continuous furnace, or a batch furnace. The pre-sintering conditions can be known conditions. For example, the conditions of maintaining at 700 to 1300° C. for 0.5 to 12 hours in an atmosphere such as air can be cited.
[0061] <Granulation process>
[0062] In the granulation step, the obtained calcined product is crushed and granulated (main granulation) to prepare a granulated product (main granulated product). The crushing method is not particularly limited. For example, a known pulverizer such as a vibration mill, a ball mill or a bead mill can be used to perform either or both of a dry method and a wet method. The granulation method can also be a known method. For example, water is added to the calcined product after crushing, and additives such as a binder resin such as polyvinyl alcohol (PVA), a dispersant and / or a defoaming agent are added as needed to adjust the viscosity, and then granulated using a granulator such as a spray dryer.
[0063] In the granulation process, the amount of binder resin and additives added is controlled to adjust the carbon (C) content in the granules to 0.001 to 0.095% by mass. It also depends on the spraying conditions described later, but by adjusting the amount of carbon (C) in the granules, the amount of α-Fe2O3 and the amount of carbon (C) in the produced ferrite powder can be controlled. That is, if the amount of carbon (C) in the granules is large, the amount of carbon (C) in the ferrite powder also tends to be large. In addition, if the amount of carbon (C) is large, the amount of α-Fe2O3 in the ferrite powder tends to decrease. This is because the atmosphere during spraying becomes more of a reducing atmosphere, so the ferritization reaction of the granules is easy to progress. Therefore, if the amount of carbon (C) in the granules is too much, it may be impossible to make the ferrite powder contain α-Fe2O3 that has the effect of suppressing the reduction of resistance. The carbon (C) content in the granules can be 0.0750% by mass or less, or it can be 0.050% by mass or less. On the other hand, if the amount of carbon (C) in the granules is too small, the amount of α-Fe2O3 in the ferrite powder becomes too large, and the magnetic properties may be reduced. The carbon (C) content in the granules may be 0.005 mass % or more, or 0.010 mass % or more.
[0064] <Spraying process>
[0065] The granules are sprayed in the spraying process. In the spraying, a mixed gas of combustion gas and oxygen is used as a combustible gas combustion flame source. The granules as the spraying raw material pass through the high-temperature combustion flame. At this time, a ferritization reaction is caused, and a part of the granules melts to become spherical ferrite particles. In the spraying, a mixed gas of combustion gas and oxygen (total oxygen content) can be used as a combustible gas combustion flame source. The volume ratio of combustion gas and oxygen (total oxygen content) is preferably 1:3.5 to 1:10.0, and more preferably 1:5 to 1:8.0. Thereby, spherical ferrite particles can be effectively produced. As the combustion gas, combustible gases such as propane gas, propylene gas, and acetylene gas can be mentioned, among which propane gas is preferably used.
[0066] In addition, the supply rate of the spraying raw material is set to 2.5 to 9.0 kg / hour. When the supply rate (supply amount) is high, the spinelization of the granulated material will progress, and the amount of α-Fe2O3 in the ferrite powder will decrease. This is because if the supply rate is high, the amount of raw material in the flame will increase and the temperature of the flame will decrease. If the flame temperature drops, the time until the particles after spraying are cooled will be shortened, and the generated divalent iron ions (Fe 2+) is likely to remain in the ferrite particles. In contrast, if the supply rate (supply amount) is low, the generation of α-Fe2O3 is likely to proceed. This is because the amount of raw materials in the flame is reduced, the temperature of the flame rises, and as a result, the time for the particles to cool after spraying becomes longer. By controlling the supply rate in this way, the amount of α-Fe2O3 in the resulting ferrite powder can be adjusted. In addition, when the supply rate is too high, the granules are likely to stick to each other, or it is difficult for the ferritization reaction to proceed fully into the particles. As a result, spherical particles cannot be obtained, or the desired magnetic properties cannot be achieved. On the other hand, when the supply rate is too low, it becomes a cause of increased manufacturing costs. From these viewpoints, the supply rate of the spraying raw material is specified in this embodiment. The supply rate can be 4.0 to 8.0 kg / hour.
[0067] The oxygen used for spraying can also be used to transport the raw material to the spraying flame. Therefore, it is divided into combustion oxygen used directly for the flame and raw material supply oxygen that is burned after the raw material is transported to the center of the spraying source. The carbon content in the ferrite powder after spraying can be controlled by the ratio of the volume of oxygen and raw material supply oxygen. Expressed as total oxygen amount = combustion oxygen + raw material supply oxygen, the preferred volume ratio is combustion oxygen: raw material supply oxygen = 95:5 to 80:20. If the ratio of combustion oxygen is greater than the above (close to 100), the raw material supply capacity is reduced, and there is a possibility that the raw material supply pipe is blocked. If the ratio of combustion oxygen is less than the above (less than 80), the raw material is widely supplied to the part deviating from the center of the highest temperature flame, so that the ferritization reaction cannot be fully carried out inside the particles. Therefore, the amount of α-Fe2O3 contained in the ferrite powder after spraying sometimes increases. From the viewpoint of not increasing the amount of α-Fe2O3 beyond necessity, combustion oxygen: raw material supply oxygen = 95:5 to 85:15 is more preferred, combustion oxygen: raw material supply oxygen = 95:5 to 87:13 is more preferred, and combustion oxygen: raw material supply oxygen = 95:5 to 89:11 is most preferred.
[0068] Furthermore, it is preferred that the combustion oxygen be set to a capacity of 0.85 times or more that required for complete combustion of the combustion gas. For example, when propane gas is used as the combustion gas, it is preferred that the combustion oxygen have a capacity of 4.25 times or more that of the propane gas. By setting in this way, even if an excess of oxygen is supplied than the oxygen required for complete combustion of the combustion gas, the temperature drop of the spraying flame can be suppressed to a minimum, and the generation of an amount of α-Fe2O3 that is more than necessary can be prevented.
[0069] In addition, the combustion gas amount ratio is preferably not less than 1.05 and not more than 2.00. Here, the combustion gas amount ratio is the amount of combustion gas used for net combustion (Nm 3 The ratio of the raw material supply amount (kg / hour) to the raw material supply amount (kg / hour) can be calculated according to the following formula (2).
[0070] [Mathematical formula 2]
[0071]
[0072] The amount of combustion gas used for net combustion (Nm 3 / hour) can be calculated using the following formula (3) or the following formula (4).
[0073] [Mathematical formula 3]
[0074] Net combustion gas volume = oxygen supplied / 5···(3)
[0075] (The amount of combustion gas supplied × 5 - the amount of oxygen supplied ≥ 0)
[0076] [Formula 4]
[0077] Net combustion gas volume = supplied combustion gas volume (4)
[0078] (When the amount of combustion gas supplied × 5 - the amount of oxygen supplied < 0)
[0079] The particles converted into ferrite by thermal spraying are rapidly cooled and solidified in an air atmosphere, and are recovered by a cyclone or a filter to obtain a thermal sprayed product.
[0080] <Grading process>
[0081] The obtained sprayed material can also be classified as needed. In the classification, the particle size can be adjusted to the desired particle size by using known methods such as wind classification (airflow classification), screening classification, and sieve classification. In addition, airflow classification such as a cyclone can separate and recover particles with larger particle sizes from particles with smaller particle sizes in one process. In this way, ferrite powder can be obtained.
[0082] According to the present embodiment, a ferrite powder having a composition and an amount of α-Fe2O3 limited within a specified range and a method for manufacturing the same are provided. The ferrite powder has high magnetic properties and electrical resistance. Therefore, even when used in a resin composition with a high filling rate, a high withstand voltage can be maintained.
[0083] Ferrite resin composite material
[0084] The ferrite powder of this embodiment can be applied to a ferrite resin composite material (resin composition). The ferrite resin composite material includes ferrite powder and resin. By using the ferrite powder of this embodiment as a filler, a composite material with excellent magnetic properties and withstand voltage can be obtained even if the filling rate of the filler is high.
[0085] As the resin constituting the composite material, for example, epoxy resin, polyurethane resin, acrylic resin, silicone resin, polyamide resin, polyimide resin, polyamide imide resin, fluororesin and / or combinations thereof can be cited. Here, the silicone resin can also be a modified silicone resin modified with acrylic acid, urethane, epoxy and / or fluorine.
[0086] The ratio of ferrite powder to the total solid content in the composite material is preferably 50 to 95% by mass, more preferably 80 to 95% by mass. In addition, the ratio of resin to the total solid content in the composite material is preferably 5 to 50% by mass, more preferably 5 to 20% by mass. By setting the ratio of ferrite powder or resin within the above range, the dispersion stability of ferrite powder in the composite material, the storage stability and formability of the composite material are excellent, and the mechanical strength or electromagnetic wave shielding performance of the composite (molded body) obtained by molding the composite material is more excellent.
[0087] The composite material may contain other components besides the ferrite powder and the resin. Examples of such components include solvents, fillers (organic fillers, inorganic fillers), plasticizers, antioxidants, dispersants, colorants such as pigments, and thermally conductive particles.
[0088] Such ferrite resin composite material can be applied to electromagnetic wave shielding material, electronic material or electronic component. Electromagnetic wave shielding material, electronic material or electronic component can be made by forming composite material with known method. The forming method is not particularly limited, for example, compression forming, extrusion forming, injection forming, blow molding or wheel rolling forming can be cited. In addition, it can also be a method in which the coating film of the composite material is formed on a substrate.
[0089] [Example]
[0090] The present invention will be described in more detail using the following examples, but the present invention is not limited to the following examples.
[0091] (1) Preparation of ferrite powder
[0092] [Example 1]
[0093] <Raw material mixing and pre-granulation process>
[0094] Iron oxide (Fe2O3) and manganese dioxide (MnO2) were used as raw materials, and the raw materials were weighed and mixed in such a way that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=8:1. A Henschel mixer was used for mixing. The obtained mixture was pre-granulated using a roller compactor to prepare a pre-granulated product.
[0095] <Pre-firing process>
[0096] The pre-granulated raw material mixture (pre-granulated material) is pre-calcined to obtain a pre-calcined material. The pre-calcination is performed using a rotary drying furnace under the conditions of 900° C.×1 hour in the atmosphere.
[0097] <Main granulation process>
[0098] The obtained calcined product was crushed and granulated to obtain a granulated product (primary granulated product). First, the obtained calcined product was milled using a dry bead mill (3 / 16 inch After coarse grinding with steel balls, water was added and the mixture was processed using a wet bead mill ( The obtained slurry has a solid content concentration of 50% by mass, and the particle size of the crushed powder (slurry particle size) is 2.367 μm. In the obtained slurry, a polycarboxylic acid ammonium salt is added as a dispersant in a ratio of 60 cc relative to 25 kg of solid content in the slurry to adjust the slurry viscosity, and then granulation is performed using a spray dryer. The volume average particle size of the obtained granules is 51.04 μm, and the carbon (C) content is 0.0511% by mass.
[0099] <Spraying and grading process>
[0100] The obtained granulated material is sprayed and quenched in a combustible gas combustion flame. During spraying, the ratio of propane gas flow rate to total oxygen flow rate is set to 1:5.42, and the ratio of raw material supply rate to combustion gas amount is set to 1.08. Next, the cooled particles are recovered by a cyclone arranged on the downstream side of the airflow to obtain a sprayed material. Furthermore, the coarse powder is removed from the obtained sprayed material using a sieve, and the fine powder is removed by airflow classification to produce ferrite powder. In the above-mentioned spraying, it is set to combustion oxygen: raw material supply oxygen = 90.8:9.2. In addition, the manufacturing conditions of ferrite powder are shown in Table 1.
[0101] [Example 2]
[0102] In the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry in a ratio of 60 cc to 25 kg of solid content in the slurry, and further, a 10 mass % aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 50 cc as a binder. Ferrite powder was prepared in the same manner as in Example 1. The granulated material obtained in the main granulation step had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass %.
[0103] [Example 3]
[0104] In the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry at a ratio of 10 cc to 25 kg of solid content in the slurry, and a 10% by mass aqueous solution of polyvinyl alcohol (PVA) was further added at an addition amount of 150 cc. Ferrite powder was prepared in the same manner as in Example 1 except that the granules obtained in the main granulation step had a volume average particle size of 50.55 μm and a carbon (C) content of 0.0743% by mass.
[0105] [Example 4]
[0106] In the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry at a ratio of 10 cc to 25 kg of solid content in the slurry, and a 10 mass % aqueous solution of polyvinyl alcohol (PVA) was further added at an addition amount of 300 cc. Ferrite powder was prepared in the same manner as in Example 1. The granulated material obtained in the main granulation step had a volume average particle size of 50.70 μm and a carbon (C) content of 0.0941 mass %.
[0107] [Example 5 (Comparison)]
[0108] In the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry at a ratio of 10 cc to 25 kg of solid content in the slurry, and a 10% by mass aqueous solution of polyvinyl alcohol (PVA) was further added at an addition amount of 600 cc. Ferrite powder was prepared in the same manner as in Example 1. The granulated material obtained in the main granulation step had a volume average particle size of 51.59 μm and a carbon (C) content of 0.0988% by mass.
[0109] [Example 6 (Comparison)]
[0110] In the raw material mixing step, the raw materials are weighed and mixed in a molar ratio of iron (Fe) and manganese (Mn) of Fe:Mn=14:1. In addition, in the main granulation step, no dispersant (polycarboxylic acid ammonium salt) is added to the slurry, and a 10 wt% aqueous solution of polyvinyl alcohol (PVA) is added in an amount of 30 cc. Furthermore, the raw material supply rate in the spraying step is set to 2.0 kg / hour. Otherwise, ferrite powder is prepared in the same manner as in Example 1. The granulated material obtained in the main granulation step has a volume average particle size of 51.17 μm and a carbon (C) content of 0.0561 mass%.
[0111] [Example 7]
[0112] In the raw material mixing step, the raw materials were weighed and mixed in such a manner that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=14:1. In addition, in the main granulation step, a dispersant (ammonium salt of polycarboxylic acid) was not added to the slurry, but a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 300 cc. Ferrite powder was prepared in the same manner as in Example 1 except for this. The granulated material obtained in the main granulation step had a volume average particle size of 50.97 μm and a carbon (C) content of 0.0971 mass%.
[0113] [Example 8]
[0114] In the raw material mixing step, the raw materials were weighed and mixed in such a manner that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=3:1. In addition, in the main granulation step, a dispersant (polycarboxylic acid ammonium salt) was not added to the slurry, but a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 30 cc. Ferrite powder was prepared in the same manner as in Example 1 except for this. The granulated material obtained in the main granulation step had a volume average particle size of 51.45 μm and a carbon (C) content of 0.0256 mass%.
[0115] [Example 9 (Comparison)]
[0116] In the raw material mixing step, the raw materials were weighed and mixed in such a manner that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=2.5:1. In addition, in the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry in a ratio of 10 cc to 25 kg of the solid content in the slurry. Ferrite powder was prepared in the same manner as in Example 1 except for the above. The granulated material obtained in the main granulation step had a volume average particle size of 50.54 μm and a carbon (C) content of 0.0549 mass %.
[0117] [Example 10 (Comparison)]
[0118] In the raw material mixing step, the raw materials were weighed and mixed in such a manner that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=2:1. In addition, in the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry in a ratio of 10 cc to 25 kg of the solid content in the slurry. Ferrite powder was prepared in the same manner as in Example 1 except for the above. The granulated material obtained in the main granulation step had a volume average particle size of 51.69 μm and a carbon (C) content of 0.0539 mass %.
[0119] [Example 11 (Comparison)]
[0120] In the raw material mixing step, the raw materials were weighed and mixed in such a manner that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=1:0. In addition, in the main granulation step, a polycarboxylic acid ammonium salt was added to the slurry at a ratio of 10 cc to 25 kg of solid content in the slurry, and a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was further added at an addition amount of 50 cc. Ferrite powder was prepared in the same manner as in Example 1 except for the above. The granulated material obtained in the main granulation step had a volume average particle size of 51.28 μm and a carbon (C) content of 0.0552 mass%.
[0121] [Example 12 (Comparison)]
[0122] In the main granulation step, a polycarboxylic acid ammonium salt is added to the slurry in a ratio of 60 cc relative to 25 kg of solid content in the slurry, and a 10 wt % aqueous solution of polyvinyl alcohol (PVA) is further added in an amount of 50 cc. In addition, in the classification step after spraying, the mesh of the sieve used to remove the coarse powder is changed, and the sieve is used to remove the fine powder. Otherwise, the ferrite powder is prepared in the same manner as in Example 1. The granulated material obtained in the main granulation step has a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass %.
[0123] [Example 13 (Comparison)]
[0124] In the spraying step, the particles are recovered by a bag filter to obtain a sprayed product. In addition, in the classification step, the coarse powder is removed from the sprayed product by air flow classification, but the fine powder is not removed. Otherwise, the ferrite powder is prepared in the same manner as in Example 12. The granulated product obtained in the main granulation step has a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass %.
[0125] [Example 14]
[0126] In the classification step after spraying, coarse powder and fine powder were removed from the sprayed product by air flow classification. Ferrite powder was prepared in the same manner as in Example 12. The granulated product obtained in the main granulation step had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass %.
[0127] [Example 15]
[0128] The mesh size of the sieve used to remove the coarse powder was further changed in the classification step after the spraying. The ferrite powder was prepared in the same manner as in Example 12. The granulated material obtained in the main granulation step had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass %.
[0129] (2) Evaluation of ferrite powder
[0130] The ferrite powders of Examples 1 to 15 were evaluated as follows.
[0131] <Component Analysis-Metal Content>
[0132] The metal content of the ferrite powder was determined by chemical analysis (ICP). First, 0.2 g of the sample (ferrite powder) was weighed, and 60 ml of pure water, 20 ml of 1N hydrochloric acid, and 20 ml of 1N nitric acid were added thereto and heated to prepare an aqueous solution in which the sample was completely dissolved. The obtained aqueous solution was placed in an ICP analyzer (Shimadzu Corporation, ICPS-10001V) to measure the metal content.
[0133] <Composition Analysis-Carbon Content>
[0134] The carbon content of the ferrite powder was measured by infrared absorption method. Specifically, 1 g of ferrite powder was burned in an oxygen gas flow to convert the carbon contained in the ferrite powder into carbon dioxide. An infrared absorption detector (LECO JAPAN Co., Ltd., carbon-sulfur analyzer CS200) was used to measure the infrared absorption of carbon dioxide, and the carbon content was calculated from the absorption.
[0135] <Component Analysis-Residual Carbon Compounds>
[0136] The residual carbon compounds of the ferrite powder were analyzed using a high-resolution mass analyzer (GC / MS). Specifically, 5 g of the ferrite powder was weighed and placed in a beaker with an internal volume of 200 ml, and 500 ml of methyl ethyl ketone (MEK) was further added. The organic components accompanying the ferrite powder were extracted by ultrasonic treatment for 5 minutes. The extracted MEK solution was filtered and the filtrate obtained was used as the test solution. The analysis conditions of the high-resolution mass analyzer GC / MS are shown below.
[0137] - Gas chromatography: Agilent Technologies, 6890N
[0138] -Mass Analyzer: Agilent Technologies, 5973N
[0139] -Column: Agilent Technologies, DB.5MS (film thickness 0.25μm)
[0140] -Heating inlet device: Parkin Elmer, Turbo Matrix 650ATD
[0141] - Temperature conditions: 50°C (2 minutes) to 280°C (18 minutes)
[0142] - Heating speed: 20℃ / min
[0143] -Carrier gas flow rate: Helium 1ml / min
[0144] -Injection method: No split 0.5
[0145] -Injection port temperature: 280℃
[0146] -Interface: 280℃
[0147] -Measurement mass range: m / z 29~600
[0148] -Injection volume: 1μl
[0149] Based on the obtained analysis results, the carbon compound was identified. The identification was performed as follows. Using an analytical device (Agilent Technologies, 5973N), the detection peaks derived from the device and from MEK were excluded from the TIC chromatogram, and the remaining detection peaks were searched in the library. The compound with the highest library consistency rate in the mass spectrum model was identified as the residual carbon compound of the ferrite powder.
[0150] <Crystalline Phase>
[0151] The ferrite powder was analyzed by X-ray diffraction to identify the crystal phase in the powder. Among the crystal phases, the content ratio of the spinel phase (Fe3O4, MnO·Fe2O3) and the α-Fe2O3 phase was determined. The analysis conditions are shown below.
[0152] -X-ray diffraction device: X'pertMPD manufactured by PA Nalytical (including high-speed detector)
[0153] -Line source: Co-Kα
[0154] -Tube voltage: 45kV
[0155] -Tube current: 40mA
[0156] -Scanning speed: 0.002° / sec (continuous scanning)
[0157] -Scanning range (2θ): 15~90°
[0158] Further analysis of the analysis results, in the crystalline phase of the ferrite powder, the content ratio of the spinel phase (Fe3O4, MnO·Fe2O3, etc.) and the α-Fe2O3 phase was obtained. The analysis was carried out as follows. That is, after removing the background and the peak of the Co-Kβ ray using the analysis software (PANalytical, High Score Plus3.0), the peak of the contour was automatically detected. For each detected peak, the half-value width and position were optimized (precision) by full spectrum fitting (Rietveld) analysis, and the content ratio of the spinel phase and the α-Fe2O3 phase was calculated based on the obtained results.
[0159] <Particle size distribution>
[0160] Determine the particle size distribution of ferrite powder. First, put 10g of the sample and 80ml of water into a 100ml beaker, and add two drops of sodium hexametaphosphate as a dispersant. Next, use an ultrasonic homogenizer (SMT Co., Ltd., UH-150 model) to disperse. At this time, set the output level of the ultrasonic homogenizer to 4, and disperse for 20 seconds. Thereafter, remove the bubbles formed on the surface of the beaker, and introduce it into a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7500nano) for measurement. Through this measurement, the 10% diameter (D10), 50% diameter (volume average particle size, D50), 90% diameter (D90) and maximum diameter (Dmax) in the volume particle size distribution are obtained. Here, the measurement conditions are set to a pump speed of 7, a built-in ultrasonic irradiation time of 30, and a refractive index of 1.70-050i.
[0161] <BET specific surface area>
[0162] The BET specific surface area of ferrite powder is measured using a specific surface area measuring device (Mountech Co., Ltd., Macsorb HM model-1208). First, about 10 g of the obtained ferrite powder is placed on a medicine paper, and the gas is removed with a vacuum dryer to confirm that the vacuum degree is below -0.1 MPa. Thereafter, the moisture attached to the surface of the particles is removed by heating at 200°C for 2 hours. About 0.5 to 4 g of the ferrite powder after the moisture is removed is placed in a standard sample chamber dedicated to the measuring device and accurately weighed with a precision balance. Next, the weighed ferrite particles are set at the measuring port of the measuring device for measurement. The measurement is performed by the 1-point method. The measurement atmosphere is set to a temperature of 10 to 30°C and a relative humidity of 20 to 80% (no condensation).
[0163] <Tap density>
[0164] The tap density of the ferrite powder was measured using a USP tap density measuring device (Hosokawa Micron Co., Ltd., Powder Tester PT-X) in accordance with JIS Z 2512-2012.
[0165] <Shape factor (SF-1)>
[0166] The average shape factor (SF-1) of the ferrite powder was obtained as follows. The ferrite powder was analyzed using a particle image analyzer (Malvern Panalytical, Morphologi G3). During the analysis, an image analysis was performed on each of the 30,000 particles in the powder, and the maximum length (horizontal Feret diameter) R (unit: μm), the projected circumference L (unit: μm) and the projected area S (unit: μm) were automatically measured. 2 ) Next, the SF-1 of each particle was calculated according to the following formula (1), and the average value thereof was taken as the SF-1 of the ferrite powder.
[0167] [Mathematical formula 5]
[0168]
[0169] <Magnetic properties - saturation magnetization, residual magnetization and coercive force>
[0170] The magnetic properties (saturation magnetization, residual magnetization, and coercive force) of ferrite powder were measured as follows. First, a chamber with an inner diameter of 5 mm and a height of 2 mm was filled with the sample and set in a vibrating sample type magnetic measuring device (Toei Industry Co., Ltd., VSM-C7-10A). The magnetic field was applied and scanned to 5 kOe, and then the applied magnetic field was reduced to draw a hysteresis curve. Based on the data of the obtained curve, the saturation magnetization (σs), residual magnetization (σr), and coercive force (Hc) of the sample were obtained.
[0171] <Magnetic properties-Magnetic permeability>
[0172] The magnetic permeability of ferrite powder was measured using an RF impedance / material analyzer (Agilent Technology Co., Ltd., E4991A) and a magnetic material measuring electrode (16454A). First, 9 g of ferrite powder and 1 g of binder resin (Kynar301F: polyvinylidene fluoride) were placed in a polyethylene container (content 100 ml), and stirred and mixed using a ball mill at a rotation speed of 100 rpm. About 0.6 g of the obtained mixture was filled into a mold (inner diameter 4.5 mm, outer diameter 13 mm), and a press was used to pressurize at a pressure of 40 MPa for 1 minute to produce a molded body. The obtained molded body was heated and cured at 140°C for 2 hours using a hot air dryer to prepare a measurement sample. The obtained measurement sample was set in the RF impedance / material analyzer, and the outer diameter, inner diameter and height of the measurement sample measured in advance were input. The amplitude was set to 100 mV, and the measurement frequency range of 1 MHz to 3 GHz was scanned using a logarithmic scale for measurement. The real part μ' and imaginary part μ" of the complex magnetic permeability at a frequency of 100 MHz were obtained, and the loss factor (tan δ) was calculated according to the following formula (5).
[0173] [Mathematical formula 6]
[0174]
[0175] <Electrical Characteristics-Volume Resistivity>
[0176] The volume resistivity of the ferrite powder was determined using a Teflon (registered trademark) container (inner diameter 17.6 mm) with an electrode attached to the bottom and an upper electrode. First, the ferrite powder was placed in a container with a height of 4 mm during the measurement and pressurized, and an electrode was installed on the upper part. The measurement was carried out under a load of 1 kg applied to the upper electrode, and an insulation resistance meter (Keithley Instrument, 6517A) was used to obtain the current flowing while the voltage was raised to 1000 V in a step-by-step manner at a 50 V scale and 5 second intervals. The relationship between the current and the applied voltage at a voltage of 100 V was obtained, and the volume resistivity was calculated.
[0177] <Electrical Characteristics-Breakdown Voltage>
[0178] When measuring the volume resistance, the applied voltage just before the output current of the measuring device (insulation resistance meter) exceeds 20 mA is obtained, and this applied voltage is taken as the breakdown voltage (V BD ).
[0179] <Resin curing properties-viscosity>
[0180] Ferrite powder is applied to resin combination, and the viscosity of resin combination is measured. First, ferrite powder 70 mass parts and host (epoxy resin) 27 mass parts and curing agent 3 weight parts are dispersed and mixed using a rotation-revolution type mixer to make resin combination. For the obtained resin, the viscosity just after making and the viscosity after 5 seconds are measured using a B-type viscometer. In addition, example 5 is due to low volume resistivity, and the evaluation of resin curing performance is not carried out.
[0181] <Resin curing properties-curing time>
[0182] The obtained resin composition was dried at 120° C. for 5 minutes. The dried resin composition was heated to 180° C. to accelerate curing, and the curing time at which the resin curing degree reached 95% or more was determined. Based on the obtained curing time, evaluation was performed as shown below.
[0183] A: Curing time is greater than std×1.00 and less than std×2.00
[0184] B: Curing time is greater than std×2.00 and less than std×3.00
[0185] Here, the so-called resin curing degree refers to the degree of progress of the curing reaction of the resin (reaction rate). The resin curing degree of the unreacted material is 0%, and the resin curing degree of the reacted material is 100%. The resin curing degree is obtained using an FT-IR (Fourier transform infrared spectrometer) device. Specifically, infrared rays are irradiated on the resin to make it pass through or split, and an FT-IR spectrum is obtained. The spectrum is used to analyze the progress of the curing reaction of the resin. In addition, the spectra of the unreacted material, the 100% reacted material, and the resin to be measured are compared, and the resin curing degree is obtained by comparing the peak intensity of each sample in the area where the difference is most observed. The curing time of Example 1 is used as the benchmark (std) to calculate the curing time of each sample.
[0186] (3) Results
[0187] The evaluation results obtained for Examples 1 to 15 are shown in Tables 2 and 3. Examples 1 to 4, 7, 8, 14, and 15 are examples of samples, and Examples 5, 6, and 9 to 13 are comparative examples of samples.
[0188] As shown in Tables 2 and 3, all samples have ferrite powder composed of true spherical particles. However, in Example 5 as a comparative example, the ferrite powder does not contain α-Fe2O3, resulting in low volume resistance and breakdown voltage, and a problem in withstand voltage.
[0189] On the other hand, in Examples 6, 11, and 13 as comparative examples, the amount of α-Fe2O3 is excessive, resulting in a low saturation magnetization (σs). On this basis, Example 13 has problems such as a small volume average particle size, too high viscosity of the resin composition, and poor resin curing performance. In Examples 9 to 11 as comparative examples, the iron (Fe) content and / or manganese (Mn) content of the ferrite powder is outside the scope of this embodiment, resulting in problems in magnetic properties (saturation magnetization, magnetic permeability, loss factor). In particular, Example 11, which contains almost no manganese (Mn) and an excess of α-Fe2O3, has a low saturation magnetization (σs), but on the other hand, the coercive force (Hc) is high, so the real part of the magnetic permeability (μ') is small, and the loss factor (tanδ) increases. In Example 12 as a comparative example, since the volume average particle size (D50) is too large, there is a problem of a high loss factor (tanδ) and a low breakdown voltage.
[0190] In contrast, Examples 1 to 4, 7, 8, 14 and 15 as embodiments are excellent in magnetic properties (saturation magnetization, coercive force, magnetic permeability, loss factor), and have high volume resistivity and withstand voltage (breakdown voltage). In particular, Examples 1 to 3, 8 and 14 did not break down during measurement and were very excellent in withstand voltage. In addition, Examples 1 to 4, 7, 8 and 15 have low viscosity when ferrite powder is applied to a resin composition. Therefore, it can be seen that it is suitable for use in a resin composition with a high filler filling rate.
[0191] [Table 1]
[0192]
[0193] [Table 2]
[0194]
[0195] [Table 3]
[0196]
Claims
1. A ferrite powder, which is a ferrite powder composed of true spherical ferrite particles, The ferrite powder contains iron (Fe): 55.0-70.0 mass % and manganese (Mn): 3.5-18.5 mass %, and the amount of α-Fe2O3 is higher than 1.0 mass % and less than 7.5 mass %, The crystalline phase of the orthospherical ferrite particles contains a spinel phase and an α-Fe2O3 phase. The α-Fe2O3 is dispersed inside the ferrite particles. The volume average particle size D50 of the ferrite powder is 15.0 μm or less.
2. The ferrite powder according to claim 1, The amount of α-Fe 2 O 3 is greater than or equal to 3.0 mass % and less than or equal to 6.0 mass %.
3. The ferrite powder according to claim 1 or 2, The volume average particle size D50 is 2.0 μm or more.
4. The ferrite powder according to claim 1 or 2, The average shape factor SF-1 of the ferrite powder is 100-110.
5. The ferrite powder according to claim 1 or 2, The ferrite powder has a carbon (C) content of 0.12 mass % or less.
6. The ferrite powder according to claim 1 or 2, The volume resistance of the ferrite powder is 1.0×10 8 Ω·cm or more.
7. A method for producing ferrite powder according to any one of claims 1 to 6, comprising the following steps: A process of mixing ferrite raw materials to prepare a raw material mixture; The process of pre-calcining the raw material mixture to obtain a pre-calcined product; A step of crushing and granulating the calcined product to obtain a granulated product; and a step of spraying the granulated material to obtain a sprayed material, The carbon content of the granulated material is set to 0.001 to 0.095% by mass. In the thermal spraying step, the raw material supply rate is set to 2.5 to 9.0 kg / hour, and the combustion gas flow rate is set to 3 to 10 m / s. 3 / hour, set the oxygen flow rate to 18~60m 3 / Hour.
Citation Information
Patent Citations
Method of manufacturing spherical powder, spherical oxide powder and oxide powder
JP2005015303A
Spherical ferrite powder, resin composition containing spherical ferrite powder and molded body using resin composition
JP2016060682A
Ferrite particles, resin composition, and resin film
WO2017169316A1
Ferrite particles, resin composition and electromagnetic shielding material
WO2017212997A1
Magnetic material and its manufacture
JP1993036515A